Human psychophysical potential quantification concept - Strizhakova, O. V.; Orlov, V. A. (Theory and Practice of Physical Culture, 2020)
Objective of the study was to analyze benefits of a human psychophysical potential quantification concept based on the standard health/ physical fitness rating tests.